1993
DOI: 10.1111/j.1600-0897.1993.tb00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Induces Expression of Endometrial Epidermal Growth Factor Receptors Before Implantation

Abstract: These results provide insight into the regulation of the autocrine and paracrine factor EGF in the endometrium during the preimplantation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…EGF and c-fos are important factors in the uterine mitogenic and weight responses to estrogen (Gonzalez et al, 1984;David et al, 1988;Weisz and Bresciani, 1988;Halling and Forsberg, 1993;Kleinstein et al, 1993). Both the uterine EGF receptor and expression of the EGF gene are under estrogen control (Mukku and Stancel, 1985;Lingham et al, 1988;Huet-Hudson et al, 1990;Astroff et al, 1990;Kleinstein et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…EGF and c-fos are important factors in the uterine mitogenic and weight responses to estrogen (Gonzalez et al, 1984;David et al, 1988;Weisz and Bresciani, 1988;Halling and Forsberg, 1993;Kleinstein et al, 1993). Both the uterine EGF receptor and expression of the EGF gene are under estrogen control (Mukku and Stancel, 1985;Lingham et al, 1988;Huet-Hudson et al, 1990;Astroff et al, 1990;Kleinstein et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Prentice et al (1992) and Chegini et al (1992) failed to demonstrate any cycle-dependent immunohistochemical staining of EGF receptors. In the rabbit Kleinstein et al (1993) showed that an increase of endometrial EGF binding was dependent only on the exposure to oestrogens, whereas progesterone showed no significant effect.…”
Section: Discussionmentioning
confidence: 95%